Flipping growth orientation of nanographitic structures by plasma enhanced chemical vapor deposition. Issue 111 (27th October 2015) - Ghosh, Subrata; Ganesan, K.; Polaki, S. R.; Ilango, S.; Amirthapandian, S.; Dhara, S.; Kamruddin, M.; Tyagi, A. K.
Abstract : Nanographitic structures (NGSs) with a multitude of morphological features are grown on SiO2 /Si substrates by electron cyclotron resonance-plasma enhanced chemical vapor deposition (ECR-PECVD). Abstract : Nanographitic structures (NGSs) with a multitude of morphological features are grown on SiO2 /Si substrates by electron cyclotron resonance-plasma enhanced chemical vapor deposition (ECR-PECVD). CH4 is used as a source gas with Ar and H2 used as diluents. Field emission scanning electron microscopy, high resolution transmission electron microscopy (HRTEM) and Raman spectroscopy are used to study the structural and morphological features of the grown films. Herein we demonstrate how the morphology of these structures can be tuned from a planar to a vertical structure using a single control parameter, namely the level of dilution of CH4 with Ar and/or H2 . Our results show that competitive growth and etching processes dictate the morphology of the NGSs. While an Ar-rich composition favors vertically oriented graphene nanosheets, an H2 -rich composition aids the growth of planar films. Raman analysis reveals the dilution of CH4 with either Ar or H2 or with the two in combination helps to improve the structural quality of the films. Line shape analysis of the Raman 2D bands shows a nearly symmetrical Lorentzian profile which confirms the turbostratic nature of the grown NGSs. This aspect is further elucidated by HRTEM studies where an elliptical diffraction pattern is observed. Based on these experiments, a comprehensive understanding is obtained of the growth and the structural properties of NGSs grown over a wide range of feedstock compositions.